TECHNOLOGY OF PEDAGOGICAL CONFLICT MANAGEMENT WITHIN AN EDUCATIONAL INSTITUTION - Sergeeva, Marina; Simonova, Natalia; Lukashenko, Dmitri; Pryazhnikova, Elena; Volkova, Yana; Samokhin, Ivan; Rozhnova, Tatiana (Revista Inclusiones, 2020)
According to the analysis of scientific and applied research on humanizing the key social development components, modern Russian scientists pay considerable attention to improving the management of objects which represent different areas of social activity (including education). Generalizing the results of studies and empirical observations allows the authors to emphasize the most common shortcomings of management systems that inhibit the accelerated development of educational systems: low science-intensive management, poor focus on modern scientific approaches to management, the use of insufficiently justified methods and procedures of management activities. Nowadays the problem of pedagogical interaction is becoming increasingly acute for educational institutions. In recent years, relations between students and teachers have become much more complicated and tense, which happens for many reasons, including age and gender issues. The relations between teachers and students undergo complex changes in each age period. The real mechanism for establishing normal relations with schoolchildren is seen in reducing the number and intensity of conflicts by transferring them into a pedagogical situation. Therefore, conflict management skills are an important tool in the teacher’s work, since the conscious application of appropriate techniques improves the quality of children’s communication, helps to preserve and develop the teaching staff and forms the teacher’s overall managerial and conflictological competence. Conflict pedagogy is currently focused on the following issues: teenage conflicts, the teacher’s conflictological competence, pedagogical intervention in conflicts, ways to prevent and resolve them.